Analisis Pelaksanaan Akad Wadi’ah Dalam Produk Simpanan - Suhrowardi; Iin Masriah; Enur Hotimah; Dede NI; Saphira VJ (JPIES: Jurnal Pelita Ilmu Ekonomi Syariah, 2024)
This research uses field research that uses descriptive qualitative methods. In the data interview, the author uses the interview method as new to the employees of BMT Fajar, Tambun Bekasi Branch, while the documentation is carried out by recording or data obtained from BMT Fajar, Tambun Bekasi Branch. ah at BMT Fajar Tambun Bekasi Branch. The results showed that wadi'ah savings at BMT Fajar were also followed by a qardhul hasan contract. In other words, in this contract the members who allow it are managed by BMT as a form of help (tabarru) in accordance with the rules of the Qur'an and hadith. Muamalah fiqh experts assess this practice as something that is permitted as long as there is no additional money as an imbalance in customer savings. From this report, the authors can report that the implementation of the wadi'ah contract in savings products is in accordance with sharia principles, but only uses different product names. But it still has to be in sharia principles.